Macro-economic Variables and Bank Performance in Nigeria: Fourth Republic Perspective - OGUNLOKUN, Ayodele; ADEBISI, Adebola Olubunmi (Journal of Entrepreneurial and Business Diversity, 2024)
Purpose: The vagaries of the macroeconomic variables make the business environment unpredictable, and this often portends mammoth implications for various businesses, primarily critical businesses such as banking, which the successive governments within the Fourth Republic have strived to protect jealously. Therefore, this study assessed the impact of macroeconomic factors on the performance of Nigerian banks from 1999 to 2021.Methodology:Data for the study period came from the World Bank reports and the CBN and SEC Statistical Bulletins. An ARDL (Autoregressive Distributed Lag) model was employed to evaluate the data.Findings: Lending interest rates had a negative and statistically insignificant impact on the performance of Nigerian banks with a coefficient of -0.0422 (p-value = 0.3860 & gt; 0.05), in contrast to the unemployment rate, which had a negative but statistically significant impact with a coefficient of -0.0534 (p-value = 0.0012 & gt; 0.05).Implication:Lending interest rate and unemployment rate impeded banks' performance, gross domestic savings, GDP per capita income, and exchange rate facilitated banks' performance in Nigeria.